Revascularization of Occluded Right Coronary Artery and Outcome After Coronary Artery Bypass Grafting - Biancari, Fausto; Dalén, Magnus; Tauriainen, Tuomas; Gatti, Giuseppe; Salsano, Antonio; Santini, Francesco; Feo, Marisa De; Zhang, Qiyao; Mazzaro, Enzo; Franzese, Ilaria; Bancone, Ciro; Zanobini, Marco; Mäkikallio, Timo; Saccocci, Matteo; Francica, Alessandra; Onorati, Francesco; El-Dean, Zein; Mariscalco, Giovanni (The Thoracic and Cardiovascular Surgeon, 2023)
Objectives The aim of the present study was to evaluate the results of isolated coronary artery bypass grafting (CABG) with or without revascularization of the occluded right coronary artery (RCA).Methods Patients undergoing isolated CABG were included in a prospective European multicenter registry. Outcomes were adjusted for imbalance in preoperative variables with propensity score matching analysis. Late outcomes were evaluated with Kaplan–Meier's method and competing risk analysis.Results Out of 2,948 included in this registry, 724 patients had a total occlusion of the RCA and were the subjects of this analysis. Occluded RCA was not revascularized in 251 (34.7%) patients with significant variability between centers. Among 245 propensity score-matched pairs, patients with and without revascularization of occluded RCA had similar early outcomes. The nonrevascularized RCA group had increased rates of 5-year all-cause mortality (17.7 vs. 11.7%, p = 0.039) compared with patients who had their RCA revascularized. The rates of myocardial infarction and repeat revascularization were only numerically increased but contributed to a significantly higher rate of MACCE (24.7 vs. 15.7%, p = 0.020) at 5 year among patients with nonrevascularized RCA.Conclusion In this multicenter study, one-third of totally occluded RCAs was not revascularized during isolated CABG for multivessel coronary artery disease. Failure to revascularize an occluded RCA in these patients increased the risk of all-cause mortality and MACCEs at 5 years.
Keywords: coronary artery bypass grafting; percutaneous coronary intervention; myocardial infarction; repeat revascularization; right coronary artery; major cardiac and cerebrovascular events